Kinetics of Phosphorous Sorption by Sediment in a Subtropical Reservoir - Wang, Xiao-Yun; Zhang, Li-Ping; Zhang, He-Si; Mei, Dao-Liang (Asian Journal of Chemistry, 2011)
The kinetics of phosphorus sorption by sediments collected from the FUSHI reservoir in China was conducted to assess the sorption process and characteristics. Experiments showed that the sorption process consisted of fast sorption, slow sorption and equilibrium stages. Duration of each stage ranged from 10 min to 10 h. The kinetic process could be described by pseudo firstorder, pseudo second-order and Evolich function. In the sorption process, ion exchange and ligand exchange were the dominant sorption actions. Sorption amount, sorption rate and sorption efficiency all increased with increasing initial concentration and decreased with extending sorption time. During the initial 0.25 h, sorption rate reached a maximum with 152.63 and 83.39 mg/(kg h-1) while concentration were 0.5 and 0.3 mg/L, respectively. About 43.10-79.36 and 37.17- 19.09 % of the sorption were completed in the fast stage and slow stage under concentration as 0.3 and 0.5 mg/L.